2022
DOI: 10.1007/s11356-022-22462-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of solar air heater performance with evacuated tubes connected in series and involving nano-copper oxide/paraffin wax as thermal storage enhancer

Abstract: The investment of solar energy in life applications has become mandatory to maintain a clean environment and reduce the use of fossil fuels. This work aimed to improve the performance of solar air heater (SAH) by using evacuated tube solar collectors ETSC integrated with nano-enhancer phase change material (NE-PCM). To achieve this purpose, a system consisting of 5 linked collecting panels was designed, fabricated, and experimentally investigated. Each panel included a glass-evacuated tube with two concentric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…When compared to evacuated tube solar water heaters, ETSACs offer the advantages of less leakage [20], inexpensive cost [24], simple construction [28], and less corrosion [29]. As they use less material, ETSACs are quite popular among all heating systems, especially in space heating and food and crop drying [30]. Furthermore, as air is directly employed as a working fluid, the number of system components required is reduced.…”
Section: Overview Of Evacuated Tube Solar Air Collectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to evacuated tube solar water heaters, ETSACs offer the advantages of less leakage [20], inexpensive cost [24], simple construction [28], and less corrosion [29]. As they use less material, ETSACs are quite popular among all heating systems, especially in space heating and food and crop drying [30]. Furthermore, as air is directly employed as a working fluid, the number of system components required is reduced.…”
Section: Overview Of Evacuated Tube Solar Air Collectorsmentioning
confidence: 99%
“…5 shows the types of ETSAC applications. Moreover, the thermal performance of ETSACs can also be enhanced by applying thermal storage, such as PCMs, which have been conducted by Elbrashy et al [30], Kalidasan et al [43], Mehla and Yadav [96], Vedanarayanan et al [97], and Dhaou et al [98], where this approach can maximize the possibility of ETSAC applications in space heating and also crop and fruit drying. In addition, PCMs have been extensively employed to overcome the two main problems caused by the intermittent nature of solar radiation: reducing energy fluctuations and storing solar thermal energy during the day and releasing it in the absence of sunlight [46].…”
Section: Rajagopal Et Al [94] Copramentioning
confidence: 99%
“…The generation of thermal energy from light is an essential physical process that not only governs all biological processes but also is of major importance for a broad variety of technologies, ranging from fundamental environmental applications like hot water generation, desalination, thermal management of buildings, , power generation, solar thermal heating, , catalysis to medical applications . For the conversion of light to heat, the photothermal effect is exploited, where light is absorbed by photothermal materials, resulting in a temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…Either by adding fins to the collector or by integrating nanoparticles instead of PCM, or else by using metal foam. Elbrashy et al [24] used an ETSC equipped with a nano-enhanced PCM (copper oxide nanoparticles with paraffin wax) at different mass flow rates to experimentally evaluate a solar air heater. The experimental findings showed that at a mass flow rate of 0.05 kg/s, the suggested ETSC attained maximum thermal efficiencies of 62.66% with PCM and 37.34% without PCM.…”
Section: Introductionmentioning
confidence: 99%